Implementation of the Biophilic Design Concept to Co-working Space in Bandar Lampung - Lestary, Aprillia Yona; Kurniawan, Panji; Jhonnata, Dona (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2025)
The current industrial revolution 4.0 has a major impact on the Indonesian economy, one of which is the emergence of startup business models. The current millennial generation is required to be able to innovate, collaborate and create new discoveries. The need for co-working space is important because it can accommodate these activities with its flexible and collaborative nature. Working indoors continuously for long periods of time can cause nature deficit disorders or reduce human well-being and can cause stress due to lack of interaction with nature. Biophilic design is a solution to reduce stress levels in workers because it has a positive impact on health. The basic concept of biophilic is to connect humans and nature in architecture. This study used descriptive qualitative method. Data collection and data analysis techniques include observation, documentation and literature study through scientific references. The design of the co-working space in Bandar Lampung aims to provide a new space for the young generation to be creative, collaborate and create new discoveries supported by a biophilic approach to reduce user stress levels and support the creative process of innovation. The basic concept of biophilic is applied well in buildings by implementing 14 biophilic design patterns.